A expansão das escolas isoladas pelo estado de São Paulo (1917-1945) - Oriani, Angélica Pall (Editora Oficina Universitária, 2022)
When proposing to write a history of isolated schools in São Paulo in the first half of the 20th century, Angélica Oriani found herself facing empirical challenges and historiographical issues. In the first case, the location of the traces left by these schools, sometimes ephemeral, supposed the attendance not only to archives and libraries, but also to teaching police stations in a pilgrimage that took the author to travel through cities in the interior of the state, such as Assis, Marília and Lins. The file was all the more necessary due to the scope of the analysis, located between 1917 and 1945/47, a period in which part of the documentation is still kept in intermediate archives and, therefore, not processed or made available for historical consultation. With regard to historiographical problems, they are of two natures Initially. refer to the very concept of isolated school. In fact, the nomenclature only came into existence when other forms of primary education appeared, such as grouped schools and school groups from 1893 onwards. Before that, in São Paulo, all primary schools were isolated, which is why constituted a specific modality of teaching But the theme also reveals a singularity of Brazilian educational historiography. In Brazil, there has never been, as there is in the US, a field of research on "urban schools"; or, as is current in Mexico, an investigation into "rural schools". Thus, studies about isolated schools sometimes get mixed up with those about rural education, despite the fact that many of these teaching units are located in urban areas, creating an indeterminacy of the research object, urgent to be overcome. The way Angélica dealt with these impasses reveals a critical and creative researcher, at the same time dedicated and sagacious, qualities that only reading this book can reveal. Diana Gonçalves Vidal - Faculty of Education USP